Western misperceptions against Islam and the Muslims an analysis - Pawan Ahmad, Isham (International Islamic University Malaysia, 2011)
The current western misconceptions against Islam is not only fueled by popular ignorance and prejudices but are also cultivated by some western scholars and writers through some subtle and not so subtle writings that have few words of praise but more focus is on prejudicial fears of Islam. This paper tries to analyze misconceptions against Islam and Muslims as created by western writers, and come up with certain ways to remove the western misconceptions against Islam and Muslims.